Microelectronic and signal processing advanced concepts and applications (CRC Press, 2021)
This book is about general and specific areas involved in electrical and electronics engineering which comprises broad subjects such as MEMS and Microfluidics, VLSI, Communication and Signal Processing. This book discusses the recent trends in various aspects of research areas for diverse applications like biomedical, biochemical, and power source systems. It also discusses modelling, simulating, and prototyping of the different electronic-based systems for carrying out varied applications. With this book, the readers will understand the multiplatform fundamentals guiding electrical and biomedical devices that form the current features such as automation, integration, and miniaturization of a particular device. This book showcases a unique platform as it covers the different areas of research in this trending era as a benchmark. This book is a link between the electronics and cutting-edge technologies that are being used for numerous applications representing the physical and virtual developments of electronic devices. Therefore, this book will mostly uphold the innovation and originality involved in the development of miniaturized devices, and proposing new methods, emphasizing with different areas of electrical and electronics engineering. This book entitles various approaches involved in electrical, biomedical, and electronics for modern distribution of research strategies and covers the state-of-art research themes. These include signal sensing, signal simulators, 3D printing technology, power systems, data acquisition systems, instrumentation, electrochemical sensing, electromechanical measurements, and signal analysis. The book will provide the academic perspectives of the cutting-edge R&D outputs from the faculty members and Ph.D. students, amalgamating the newer cross-dimensional areas, such as cyber-physical systems, nanoelectronics, smart-sensors, point-of-need devices, etc. The book will become a benchmark to the readers to understand the academic aspect of the contemporary work and the way forward on how this will lead to help the society-at-large.